VI Certamen Crono-Teatro (2019). Modalidad del tren. 4. Siéntese - García Pérez, Marcos (Pygmalion. Revista de teatro general y comparado, 2025)
VI Certamen Crono-Teatro (2019). Modalidad del tren. 4. Siéntese